APPLICATION AND COMPLIANCE WITH THE MEDICAL STANDARDS IN THE FIELD OF OBSTETRICS, GYNECOLOGY AND RELATED SPECIALTIES IN BULGARIA - Ivan Kostov; Gergana Ingilizova; Sergei Slavov (Peytchinski Publishing, 2023)
This study has examined and analyzed the public information on inspections performed by the Executive Agency "Medical Supervision" (EAMS) of hospitals in the country - specialized obstetrics and gynaecology hospitals and departments in multidisciplinary hospitals related to Obstetrics and gynaecology (OG), oncogynaecology, neonatology and reproductive medicine for a period of three years (2014 - 2016) in order to establish the presence, frequency and causes of malpractices of the requirements of the relevant medical standard. Materials and methods: The results of 74 inspections under the medical standard and 29 mixed in 125 medical institutions were analyzed. Results: In most of the inspections carried out by the Executive Agency "Medical Supervision", no malpractices of compliance with medical standards were found. The established malpractices under the medical standard mainly concerned obstetrics and gynaecology care and the standard of OG - 57,3% and to a much less extent the standards of neonatology and assisted reproduction - 13,6% for each. The largest part of the deviations in medical standards in OG (p <0.05) concerned the accurate maintenance and filling in of the medical documentation - 26.0%, insufficient operational activity - 21.5% and staff qualifications - 18.8%. The main problem in neonatology was the number of medical staff, and in assisted reproduction - 24 hours of continuity of service. Conclusions: As of date the research outlines the need for future actions to revise the current medical standards in OG, assisted reproduction and neonatology, mainly in terms of how the standard works, whether it needs updating and to what extent it is accepted by the profession.